PELATIHAN EFEKTIFITAS OPERASIONALISASI PEMBERKASAN SURAT BAGI PEGAWAI DI KANTOR KEPALA DESA CITERAS KEC. RANGKASBITUNG KAB. LEBAK -- BANTEN - Rosali Sembiring; Nurhafifah Matondang (Madani: Jurnal Pengabdian kepada Masyarakat, 2021)
Each company must manage the administration of existing letters in the company / office effectively so that it does not interfere with company operations. Procedures are a series of tasks that are integrated in an integrated manner with one another.